Survivin a pivotal antiapoptotic protein in rheumatoid arthritis. Issue 12 (6th May 2019) - Zafari, Parisa; Rafiei, Alireza; Esmaeili, Seyed‐Alireza; Moonesi, Mohammadreza; Taghadosi, Mahdi
Abstract: Rheumatoid arthritis (RA) is an autoimmune disease, pathologically characterized by lymphocyte infiltration of the synovial membrane that leads to chronic inflammation and progressive joint damage. RA develops as a result of increased cell infiltration and cell proliferation as well as impaired cell death. Activated cells in joints including lymphocytes and fibroblast‐like synoviocytes (FLS) survive for a long time as a consequence of compromised apoptosis, but the mechanism underlying cell survival in synovium remains to be firmly established. Inhibition of apoptosis by survivin, as a critical antiapoptotic protein, contributes to both the persistence of autoreactive T lymphocytes and tumor‐like phenotype of FLS in RA. In addition to the antiapoptotic role, survivin also has prognostic relevance in RA prodromal phase. Hence, this review provides an overview of the current knowledge regarding the involvement of survivin protein in the pathogenesis of RA. Abstract : Rheumatoid arthritis (RA) is characterized by lymphocyte infiltration of the synovial membrane that leads to chronic inflammation and progressive joint damage. RA develops as a result of increased cell infiltration and cell proliferation as well as impaired cell death. Inhibition of apoptosis by survivin, as a critical antiapoptotic protein, contributes to both the persistence of autoreactive T lymphocytes and tumor‐like phenotype of fibroblast‐like synoviocytes in RA. In addition to the antiapoptotic role, survivin also has prognostic relevance in RA prodromal phase. Hence, this review provides an overview of the current knowledge regarding the involvement of survivin protein in the pathogenesis of RA.